Preconceito contra a diversidade sexual: análise dos relatos de duas coordenadoras pedagógicas acerca da formação desenvolvida na escola - Messias, Tiago Monteiro de (2017)
The present research aims to analyse the reports of the formative training proposals that were developed by two pedagogical coordinators of a public school in relation to the prejudice against sexual diversity. We seek to reflect on this training process based on the pedagogical coordinators' perceptions, in order to instigate more sustained views on teacher training in this area. For the research, we performed this analysis based on relate of practices. The coordinators’ reports, collected from semi-structured interviews, gave us an input for the elaboration of analytical boxes, which are the basis for the reasoned analysis of the practice. Among the theoretical references used in this dissertation, to discuss about sexuality, we focus on Foucault (1984) and Louro (1999); in the light of Imbernón (2000; 2010) and Placco e Souza (2006) we address teacher training, challenges and possibilities in the teacher's professional development work; and, to discuss about social representations, we discuss with emphasis on the proposals of Abric (1994) and Moscovicci (1978).Based on the results of the analyses of the pedagogical coordinators’ reports, it is evident that it is essential to discuss what underlies the prejudice, so that we can move more assertively into the discussion about prejudice against sexualities and it is also essential a critical and careful view as regards to formal training proposals in the school